THE ROLES OF UNIVERSITY TEACHERS IN BUILDING TEACHER STUDENTS’ CAPACITY OF REFLECTIVE PRACTICE THROUGH THE PROCESS OF EXPERIENTIAL LEARNING - Zavadskienė, Loreta; Bubnys, Remigijus (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
As the carried-out research study shows, proper interpretation of the concepts of reflective learning, the reflective practitioner and the experiential learning theory in the context of higher teacher education provides a solid theoretical background for the analysis of the teaching-learning process of pre-service teachers’ reflective practice and the support to be provided by teacher educators. By employing the method of the scientific literature review, the current research paper aims to investigate the roles of teacher educators within the framework of the afore mentioned theories that are considered to ensure adequate assistance to pre-service teachers in their becoming reflective practitioners. As the results show, in order to carry out effective facilitation, teacher educators should acknowledge and adopt a wide variety of roles while developing pre-service teachers’ capacity of reflective practice.